Chemotherapy-induced neutropenia among breast Cancer patients in a tertiary care hospital: Risk and consequences. (April 2023) - Joseph, Anu; Joshua, Julie Mariam; Mathews, Santhosh M
Study objective: To identify the risk factors that may predispose breast cancer patients to Chemotherapy-induced neutropenia (CIN) and its associated complications for the years 2018 and 2020. CIN is an established complication of breast cancer treatment. Clinical Pharmacists can play an important role in the treatment of CIN through involvement in risk assessment to identify patients for oral antimicrobial therapy, drug therapy monitoring, and development of suitable guidelines or policies. Methodology: A retrospective study was performed by collecting data of 72 breast cancer patients for the last two years from department of Medical Oncology in a tertiary care hospital. Results: The overall occurrence of CIN was 59.7% in our study population. Out of 72 patients studied, 43 patients were found to be neutropenic. Using Pearson Chi square test, chemotherapy-induced neutropenia was associated with older age (over 60 y) ( p < 0.038), diabetes mellitus ( p < 0.050), tumour stage IIIa ( p < 0.024), AC ( p < 0.051) and taxane chemotherapy regimens ( p < 0.041). Febrile neutropenia occurred in 37.28% of patients and the incidence of infection-related mortality [severe septicaemia] was 3.38%. Conclusion: The incorporation of clinical pharmacist must be brought into practice in our country for providing proper guidance to the patient on CIN and its complications. By identifying risk factors for neutropenia, the safe management of CIN may be possible in patients with breast cancer.